(untitled) (Journal of Pathology of Nepal, 2021)
Mucinous carcinoma with a micropapillary pattern is an unusual form of Invasive breast cancer exhibiting dual mucinous and micropapillary differentiation. The present case is of a 47-year-old nulliparous female who presented with an incidental finding of a hard lump in her left breast. Mammography revealed a BIRADS 4 lesion. Modified radical mastectomy was done and the specimen was grossed, revealing a tumor of 3x2.6x2.6 cm in the outer quadrant. Microscopy revealed the tumor having extracellular mucin pools with floating psammoma bodies and focal micropapillary pattern. Four of the twenty-six lymph nodes sampled were found to have tumor deposits. The micropapillary pattern was maintained in the metastatic deposits. Immunohistochemistry revealed ER and PR positivity and Her2Neu negativity. EMA corroborated the findings. It is important to recognize the micropapillary pattern in mucinous carcinomas of the breast as these tumors tend to be more aggressive than pure mucinous breast lesions.